β-Cell Failure or β-Cell Abuse? - Erion, Karel; Corkey, Barbara E. (Frontiers in Endocrinology, 2018)
This review is motivated by the need to question dogma that has not yielded significant improvements in outcomes of Type 2 Diabetes treatment: that insulin resistance is the driver of ß-Cell failure and resulting hyperglycemia. We highlight the fact that hyperlipidemia, insulin resistance and hyperinsulinemia all precede overt diabetes diagnosis and can each induce the other when tested experimentally. New research highlights the importance of high levels of circulating insulin as both a driver of weight gain and insulin resistance. Data from our lab and others document that several nutrients and environmental toxins can stimulate insulin secretion at non-stimulatory glucose in the absence of insulin resistance. This occurs either by direct action on the ß-Cell or by shifting its sensitivity to known secretagogues. We raise the next logical question of whether ß-Cell dysfunction in Type 2 Diabetes is due to impaired function, defined as failure, or if chronic overstimulation of the ß-Cell that exceeds its capacity to synthesize and secrete insulin, defined as abuse, is the main abnormality in Type 2 Diabetes. These questions are important as they have direct implications for how to best prevent and treat Type 2 Diabetes.